Low patronage of development radio programmes in rural Nigeria: How to get beyond the Rhetoric of participation (2008)
Although the concept of participatory development communication is decades old, many years of autocratic military rule has robbed African scholars and media practitioners of the context needed to explore the full participatory potentials of the media. With eight years of democracy and heavy development burdens, Nigeria is ripe for assessment with regard to the role of its media in engendering participatory development. From a small-scale study, this paper discovers that while radio stations expend tremendous time and energy producing and airing development programmes, the listeners in the selected rural area mostly avoid such programmes and spend their time and batteries on a strange genre of programmes tagged ‘bizarre occurrence’ programmes. This implies that the listeners are not properly taken into account, let alone involved in the production of these development programmes. This is clearly contrary to the tenets of participatory development communication and democracy. The paper suggests ways by which radio can become a more participatory medium with its mission, focus and products consistent with the democratic dispensation.